KEEFEKTIFAN PENDEKATAN REALISTIC MATHEMATICS EDUCATION DENGAN METODE DRIL TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS III SD - Widodo Hadi Pratomo (Universitas Muhammadiyah Surakarta, 2016)
The problem of this research is does the approach of realistic mathematics education with drill method is effective against mathematics learning outcomes third grade students of SDN Peterongan Semarang in the academic year 2016/ 2017? Based on the problems posed hypotheses as follows: realistic approach to mathematics education with drill method is effective against mathematics learning outcomes third grade students of SDN Peterongan Semarang academic year 2016/ 2017. The goals to be achieved in this study was to determine the effectiveness of the approach is realistic mathematics education methods drill on learning outcomes third grade students of elementary mathematics N Peterongan Semarang in the school year 2016/ 2017. this type of research is quantitative. The population in this study were students of class III Elementary School Peterongan Semarang. The sample class III A control group of 32 students and class III B as an experimental group of 32 students. Experimental research design using a true experimental design, shape chosen is posttest only control group desaign. Data collection tool used is multiple choice test. The results of the t test analyzes is one side (right side) obtained t arithmetict table is 5.4611.670, then Ho is rejected. Thus, the realistic approach to mathematics education with drill methods have the significant difference to student learning outcomes experimental class control class. Acquisition of individual mastery learning in the experimental group that is 100% and the average value of 84.218. A control group with a percentage of 87.5% and the average value of 73.718. So it can be concluded that the approach of realistic mathematics education with drill method is effective against mathematics learning outcomes third grade students of SDN Peterongan Semarang.